Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2174/0929867323666161024150540
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clusterin in Carcinogenesis and its Potential Utility as Therapeutic Target

Abstract: Clusterin is a glycoprotein that has been implicated in many processes, including apoptosis, cell cycle regulation and DNA repair. Since clusterin expression has also been associated with tumorigenesis and the progression of various malignancies including prevalent tumors like prostate, colon, bladder and breast, this protein has been proposed as a good candidate for future treatments. There have been numerous studies conducted in cell lines and xenograft models with successful results that, in general, justif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…88 It may be induced by stress and was identified as a cytoprotective chaperone protein that aids folding of secreted proteins. The three isoforms of APOJ were discovered to participate in pro-and antiapoptotic processes 89 and were abnormally regulated in many severe physiological disturbances including cancer initiation and progression. 90 Combined with other chemotherapeutic agents, antisense compounds targeting APOJ proved successful in clinical trials for the treatment of prostate cancer.…”
Section: Apolipoprotein J and Cancermentioning
confidence: 99%
“…88 It may be induced by stress and was identified as a cytoprotective chaperone protein that aids folding of secreted proteins. The three isoforms of APOJ were discovered to participate in pro-and antiapoptotic processes 89 and were abnormally regulated in many severe physiological disturbances including cancer initiation and progression. 90 Combined with other chemotherapeutic agents, antisense compounds targeting APOJ proved successful in clinical trials for the treatment of prostate cancer.…”
Section: Apolipoprotein J and Cancermentioning
confidence: 99%
“…Concerning the mechanism of CLU expression, although it is not so clear currently, but influenced by cytokines, growth factors as well as stress ones such as oxidative stress, heat shock, chemotherapy and radiotherapy [14,17] . According to previous reports, the tolerance to chemotherapy and radiotherapy is closely related with CLU expression in several cancers, and CLU up-regulation has been confirmed in many cancers including prostate, kidney, bladder, breast, head and neck, colon, cervical, pancreatic, lung, melanoma lymphoma [16,18] . Therefore, CLU has been considered as a biomarker for tumour malignancy, and it is believed that improvement of tumour cell sensitivity to chemotherapy and radiotherapy is promising way to control cancer by reducing CLU expression [14,[19][20][21] .…”
Section: Discussionmentioning
confidence: 90%
“…sCLU is a highly glycosylated multifunctional protein, which is widely expressed in a variety of mammalian tissues and participates in many physiological processes, such as cell cycle regulation, DNA repair, and angiogenesis [15] . Recent studies have shown over-expression of CLU in several cancers, whose blocking enhances tumour cell sensitivity to chemotherapy and radiotherapy, therefore, CLU has become an important therapeutic target for cancer treatment [14,16] .…”
Section: Introductionmentioning
confidence: 99%
“…The cytoprotective chaperone protein clusterin (CLU) is involved in multiple physiological processes associated with carcinogenesis and tumor growth, including apoptotic cell death, cell cycle regulation, DNA repair, cell adhesion, tissue remodeling, lipid transport, membrane recycling, and immune system regulation [3,4]. As the major isoform, secretory apolipoprotein J (s)CLU has been extensively investigated in the context of tumor diagnosis and prognosis owing to its antiapoptotic function.…”
Section: Introductionmentioning
confidence: 99%